A critical review on cathode materials for steam electrolysis in solid oxide electrolysis. (22nd April 2023) - Biswas, Saheli; Kaur, Gurpreet; Paul, Gary; Giddey, Sarbjit
Abstract: The major technologies being considered for the green hydrogen production are polymer electrolyte membrane (PEM) and solid oxide electrolysis (SOE). While PEM electrolysis technology is nearing commercialisation with units now being globally installed at tens of MW scale, SOE technology is still under development with units available only at 100s of kW scale and at much higher costs per kW. SOE due to its high operating temperatures (close to 800 °C) has the potential to reduce the electric energy input by up to 30% for the hydrogen production per tonne by using the low-cost thermal energy input available from the industrial or downstream synthesis processes. The SOE cathode, where steam electrolysis occurs, plays a crucial role in dictating the cell voltage losses and the stability of the cell operation that eventually has a large impact on the SOE efficiency and lifetime. The current state-of-the-art cathode materials based on Ni-YSZ pose many challenges. There is, therefore, a global effort to find alternative cathode materials suitable for steam electrolysis in SOE. This review critically reviews novel nanoengineered cathode materials and points to the fact that such materials synthesized using infiltration and exsolution techniques, in combination with advanced materials characterisation like high-temperature scanning probe microscopy and in situ Raman spectroscopy can be a right approach to find the suitable cathode materials for steam electrolysis in SOE. This, however, may need to be combined with a techno-economic analysis to provide the technical and economic viability of these materials for the SOE commercialisation. Graphical abstract: Image 1 Highlights: High temperature steam electrolysis critically reviewed, focussing on cathode materials. Conventional and alternative cathode materials briefed, and their challenges discussed. Novel heterostructured materials and their drawbacks discussed in-depth. Scope of further research around novel materials highlighted at the end.